2022
DOI: 10.48550/arxiv.2205.03895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Sea-Level Change in Coastal Areas

Abstract: Variations in sea-level, based on tide gauge data (GSLTG) and on combining tide gauges and satellite data (GSLl) are subjected to singular spectrum analysis (SSA), to determine their trends and periodic or quasi-periodic components. GLSTG increases by 90 mm from 1860 to 2020, a contribution of 0.56 mm/yr to the mean rise rate. Annual to multi-decadal periods of ∼ 90/80, 60, 30, 20, 10/11, and 4/5 years are found in both GSLTG and GSLl. These periods are commensurable periods of the Jovian planets, combinations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Such a link would not be favored, as illustrated by various interpretations suggested in the past (e.g., Lyons, 1899;Jensen, 1902;Schneider and Mass, 1975;Mazzarella and Palumbo, 1988;1989;Stothers, 1989;Strestik, 2003;Herdiwijaya et al, 2014;Vasilieva and Zharkova, 2020). Dumont et al (2022) have identified a link between global volcanic eruptions and the global mean sea level, which is known to exhibit planetary-scale periodicities (Le Courtillot et al, 2022a). Such a link can be understood in the case of insular, submarine and coastal magmatic plumbing systems, which are the most abundant (Dumont et al, 2022): stress variations can be induced by pressure changes imposed by oceanic water mass transport at different timescales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a link would not be favored, as illustrated by various interpretations suggested in the past (e.g., Lyons, 1899;Jensen, 1902;Schneider and Mass, 1975;Mazzarella and Palumbo, 1988;1989;Stothers, 1989;Strestik, 2003;Herdiwijaya et al, 2014;Vasilieva and Zharkova, 2020). Dumont et al (2022) have identified a link between global volcanic eruptions and the global mean sea level, which is known to exhibit planetary-scale periodicities (Le Courtillot et al, 2022a). Such a link can be understood in the case of insular, submarine and coastal magmatic plumbing systems, which are the most abundant (Dumont et al, 2022): stress variations can be induced by pressure changes imposed by oceanic water mass transport at different timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to short-term timescales and tidal periodicities, these multi-annual to centennial variations are present in other geophysical parameters. Most of them record both tidal and solar periodicities, as illustrated by the magnetic field (e.g., Bartels, 1932;Le Mouël, 1984;Courtillot and Le Mouël, 1988;Jault, 1990;Le Mouël et al, 2019), polar motion (Lopes et al, 2017;Lopes et al, 2021a;Lopes et al, 2022a), sea level observed from local and global data (e.g., Chambers et al, 2012;Wahl and Chambers, 2015;Le Mouël et al, 2021a;Courtillot et al, 2022a), global surface air temperatures (e.g., Courtillot et al, 2013;Le Mouël et al, 2020b;Scafetta, 2021), and more generally, climate (e.g., Wood and Lovett, 1974;Schlesinger and Ramankutty, 1994;Scafetta, 2010;Courtillot et al, 2013;Scafetta, 2016;Le Mouël et al, 2019c;Le Mouël et al, 2021b). Moreover, these links also seem to exist 1) on much longer timescales of millennia, governed by astronomical configurations and impacting climate and sedimentation (e.g., Milanković, 1920;Kutterolf et al, 2013;Coussens et al, 2016;Kutterolf et al, 2019;Lopes et al, 2021b;Satow et al, 2021); and 2) also for earthquakes, as suggested by numerous studies (e.g., Tamrazyan, 1968;Mazzarella and Palumbo, 1988;Marchitelli et al, 2020).…”
Section: Periodicities Detected In Volcanic Activity and Other Geophy...mentioning
confidence: 99%